Factors Influencing Online Purchase Intention with The Mediating Role of Customer Satisfaction - Ur Rehman, Shafique; Bano, Talat; Bhatti, Anam (International Journal of Economics, Management and Accounting, 2019)
The purpose of the paper is to determine the mediating role of customer satisfaction between celebrity endorsement, brand equity, corporate social responsibility and online purchase intention in Pakistan. Some 600 questionnaires were distributed among consumers for data collection through convenience sampling. Out of these, 398 questionnaires were returned, 14 questionnaires had some missing values and were removed from the sample; only 384 questionnaires were finally used in the analysis. Punjab has a total of 36 districts and data were collected from 16 districts having the majority of the population. PLS-SEM was used for data analysis. Results reveal that only celebrity endorsement has a direct influence on online purchase intention. Furthermore, independent variables have a significant influence on customer satisfaction. Customer satisfaction significantly mediates between celebrity endorsement, brand equity, corporate social responsibility, and online purchase intention. This study contributes to practice in that online retailers can consider celebrity endorsement, brand equity, corporate social responsibility, and customer satisfaction in their decision to enhance online purchase intention. This paper is one of the pioneer studies that determine celebrity endorsement, brand equity, and corporate social responsibility at second-order with customer satisfaction as a mediating variable with online purchase intention.